2016
DOI: 10.4103/0019-5545.192016
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine has better efficacy compared to risperidone for treatment of negative symptoms in schizophrenia

Abstract: Objective:The safety and efficacy profile of risperidone and olanzapine were compared in a double-blind trial that used doses widely accepted in clinical practice.Methods:Subjects (n = 71) who met Diagnostic and Statistical Manual of Mental Disorders-IV criteria for schizophrenia were randomly assigned to receive 2–8 mg/day of risperidone (mean modal dose = 5.5 mg/day) or 5–20 mg/day of olanzapine (mean modal dose = 14.4 mg/day) for 1 year.Results:The two study groups were similar at baseline in all aspects. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This difference was because Shah et al (2011) used participants with the outpatient method, so the physical activity and the dose of drugs could not be fully controlled while the study by Conley et al (2001) used participants who were hospitalised. Nevertheless, Tran et al (1997) [ 9 ] and Kumar et al (2016) [ 10 ] who recruited participants who were hospitalised also found similar results to the results of Shah et al (2011) [ 8 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This difference was because Shah et al (2011) used participants with the outpatient method, so the physical activity and the dose of drugs could not be fully controlled while the study by Conley et al (2001) used participants who were hospitalised. Nevertheless, Tran et al (1997) [ 9 ] and Kumar et al (2016) [ 10 ] who recruited participants who were hospitalised also found similar results to the results of Shah et al (2011) [ 8 ].…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, the positive scale and the total score between the two groups were found to be comparable [ 8 ]. Similarly, Shah et al (2011) and Kumar et al (2016) reported that although the improvement in the negative scale was significantly higher in the group treated with olanzapine, there were no significant differences for the positive scale and the total score of PANSS in both groups [ 9 ] [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the cholinergic system are seen in schizophrenia, with the majority of findings indicating decrements in cholinergic neurotransmission [56,57]. The antipsychotic medications olanzapine and clozapine modulate cholinergic neurotransmission, and have both the greatest efficacy in treatment-resistant schizophrenia, and reductions in severity of negative symptoms [58]. Additionally, nicotine alters cholinergic signaling, increases global BDNF levels, and is highly used in persons with schizophrenia [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Suresh Kumar et al . [ 1 ] randomized patients with schizophrenia ( n = 71) to receive either olanzapine (mean modal dose, 14.4 mg/day) or risperidone (mean modal dose, 5.5 mg/day) for 1 year. They reported that olanzapine was associated with significantly greater improvements in negative symptom ratings at all follow-up visits, that is, at months 3, 6, 9, and 12.…”
mentioning
confidence: 99%
“…In research, primary and secondary outcomes should be stated a priori, and greater emphasis should be laid on the former than on the latter. [ 2 ] There was no indication whatsoever that the authors[ 1 ] intended to study negative symptoms as their primary outcome.…”
mentioning
confidence: 99%